Generation Z in Plastic Surgery: Challenges, Solutions and New Horizons – A European and transatlantic overview - Giunta, Riccardo E.; Bassetto, Franco; Demirdöver, Cenk; Evans, Gregory R.D.; Henley, Mark; Kaartinen, Ilkka; Lehnhardt, Marcus; Masia, Jaume; McArthur, Paul; Saboye, Jacques; Steubing, Yonca; Aranda, Irene Mesas (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2025)
Introduction  The entrance of Generation Z (born 1997–2012) into professional life, including the practice of medicine, marks a transformational shift in priorities and values. This generation, shaped by digital immersion and a strong focus on work-life balance, is redefining the landscape of Plastic Surgery. Their preferences for inclusivity, innovation, and structured working hours challenge traditional models of mentorship, patient care, and surgical training. The aim of this survey was to explore the impact of Generation Z on the field of Plastic Surgery through insights offered by leaders of major Plastic Surgery societies in Europe and the United States, who together provide a comprehensive perspective on generational change and its implications for clinical practice, education, and healthcare systems in Plastic Surgery.Methods  In October 2024 eight leaders of national Plastic Surgery societies and associations were invited to complete a structured questionnaire with five open-ended questions. They provided detailed responses on challenges, opportunities, and structural changes needed to address Generation Zʼs influence.Results  Key findings highlight a generational shift in the approach to professional life, with an emphasis on digital innovation, work-life balance, and the interaction with social media. Respondents noted an increased interest in aesthetic over reconstructive surgery and a preference for private practice among younger surgeons, raising concerns about workforce shortages in public healthcare. Advances in digital learning and simulation-based training were identified as opportunities to facilitate medical education. However, the ethical challenges of misinformation on social media and a decline in hierarchical mentorship were emphasized as critical concerns. Despite generational tensions, the integration of Generation Z’s strengths in technology and advocacy for systemic reform holds promise for addressing burnout and enhancing healthcare delivery.Conclusion  The arrival of Generation Z in Plastic Surgery represents a possible pivotal moment to reimagine traditional models of surgical education, patient care, and professional priorities. Collaboration between generations and proactive adaptation to these changes is an imperative to ensure a dynamic, inclusive, and sustainable future for the specialty.
Keywords: Generation Z; Plastic Surgery; digital innovation; work-life balance; surgical education; generational shift; healthcare systems